FEMINISME ISLAM: Perspektif Islam Kontemporer - Muqoyyidin, Andik Wahyun (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractGender is one of a number  of contemporary  discourse that can be called that is enough  to  get  the  attention  of  many  people,  from  the  teenagers, among movement  activists, academics and students, the legislature and government,  to the clergy. The purpose of this discourse is a close social injustice based on gender differences, the next attempt to bring about equality between men and women on the social aspects. Gender discourse can be categorized into at least four appearances, namely as a movement, a philosophical discourse, the development of social issues to religious issues, and as an approach in the study of religion. This paper  will discuss the perspectives of gender equality as conceived by Muslim feminists. Generally it can be stated that the goal of feminism is the struggle to achieve equality, dignity, and freedom of women in selecting and managing the life and body, both inside and outside the household.Kata Kunci:  kesetaraan, gender, gerakan, feminisme Islam